2015
DOI: 10.5897/ajfs2015.1279
|View full text |Cite
|
Sign up to set email alerts
|

Drying by spray drying in the food industry: Micro-encapsulation, process parameters and main carriers used

Abstract: The process of spray drying consists of the transformation of a product in fluid form to the solid state in the form of powder. This is done through the dispersion of droplets from the product inside a chamber, in contact with hot air. In this process, substances known as carriers or encapsulating agents can be added, aiming at facilitating or even allowing the drying of certain products. The objective of this review was to approach the most important technological aspects of the drying by technique for the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 32 publications
1
40
1
15
Order By: Relevance
“…Studies have shown that maltodextrin is able to preserve antioxidant activity. It is also well known that the antioxidant activity depends on the oxidative stability of each of the carriers, something that has been reported as a characteristic of gum arabic (Costa et al, 2015).…”
Section: Antioxidant Capacitymentioning
confidence: 98%
“…Studies have shown that maltodextrin is able to preserve antioxidant activity. It is also well known that the antioxidant activity depends on the oxidative stability of each of the carriers, something that has been reported as a characteristic of gum arabic (Costa et al, 2015).…”
Section: Antioxidant Capacitymentioning
confidence: 98%
“…Because the spray-drying technique is relatively old (on an industrial scale it dates back to the 1920s), there are many variations in its set-up [29]. The final product quality depends on the operating conditions, such as inlet and outlet air temperatures, feed flow rate, and spraying speed and pressure [29,30].…”
Section: Spray-dryingmentioning
confidence: 99%
“…In order to obtain any useable powder the addition of a carrier material to the juice is necessary (Janiszewska, 2014). In this study, maltodextrin (MD), arabic gum (AG) and rice starch (S) were chosen as the most commonly used carriers for the spray drying of fruit juices in the food industry (Costa et al, 2015;Janiszewska-Turak et al, 2017). Moreover, mixtures of these carriers are usually better for protection than the usage of one carrier material only (Fazaeli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%